Influence of sGnRH-a + Domperidone With Different Doses for Ovulation Stimulation, Egg and Larvae Quality of The Pawas (Osteochilus hasselti CV) - Septiana Anggraini; Sukendi '; Netti Aryani (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This research was conducted over 60 days, starting on April 20 until June 8 2015, at the Hatchery and Breeding Laboratory at Fisheries and Marine Science Faculty, University of Riau. This research aims to determine the effect of sGnRH-a + domperidone with different doses of the ovulation stimulation and the eggs quality of Nilem Carp (O. hasselti CV) which is the first step of research and then the best dosage obtained through observations in the first step will then be injected against gonads mature female brood and then will spawn with the male injected with the best dose (0.4 ml/kg body weight) through research "sGnRH-a + domperidone With Different Doses for Volume, Concentration and Cement Quality of Nilem Carp (O. hasselti CV) as the second step of this research. The results showed that sGnRH-a + domperidone at a dose of 0.6 ml/kg body weight were significant (p<0,05) for the latent time, total eggs ovulation, egg diameter increase, eggs maturity and ovisomatik index value, with the best results for the latent time (6.15 hours), total eggs ovulation (242 eggs/g gonads), egg diameter increase (0.9125 mm), eggs maturity (20 %) and ovisomatik value index (14.75 %). Results of the second step resulted in average: fertility rate (81.33 %), hatching rate (81.76 %), absolute length growth (1.91 cm), absolute weight growth (0.27 g), daily growth rate (10.17 %) and the rate of survival (95.1 %). Keywords : sGnRH-a + Domperidone, Ovulation Stimulation, Nilem Carp (Osteochilus hasselti CV).